STRATEGI KOMUNIKASI DIVISI MEDIA RELATIONS DALAM MENGHADAPI ISU PUBLIK STUDI KASUS PT XYZ - Hanania Adinda; Hudi Santoso (Halu Oleo University, 2025)
This study aims to analyse the communication strategies of PT XYZ's Media Relations Division in dealing with public issues that could potentially affect the company's reputation. As an upstream oil and gas company operating in an area prone to environmental, social, and safety issues, PT XYZ faces complex communication challenges in the digital age. This study uses a descriptive qualitative approach with case studies to describe in depth the process of planning, implementing, and evaluating the communication strategies applied. The results show that PT XYZ's communication strategy refers to the Situational Crisis Communication Theory (SCCT) framework, which includes three main approaches: diminish strategy, rebuild strategy, and bolstering strategy. The diminish strategy is used for incidental issues with an emphasis on fact-based clarification; rebuild is applied to situations that have a social impact through corrective actions and empathetic communication; while bolstering is carried out through strengthening relationships with the media and implementing corporate social responsibility (CSR) programs. The application of these three strategies has proven effective in maintaining positive public sentiment, increasing trust, and strengthening the company's reputation. This study emphasises the importance of internal coordination, information transparency, and empathy-based communication as the keys to successful public issue management in the energy sector.